SISTEM INFORMASI INVENTORI UMKM BUNDA CAHYO CATERING - heri nuryanto; Miratia Afriani; Hari Sandi Atmaja; Eryd Saputra (Universitas Putera Batam, 2026)
Bunda Cahyo Micro, Small, and Medium Enterprises (MSMEs) is a catering business that handles various food orders for celebrations, parties, and other events in the city of Batam. In running its business, inventory management issues have become a major obstacle. This study aims to develop an inventory information system based on Microsoft Excel Visual Basic for Applications (VBA) designed to record inventory transactions. The method used in developing the system is the Waterfall model, which includes the stages of requirements analysis, menu design, VBA coding, program testing, and maintenance. The results of the study show that the inventory system can be effectively implemented and operates without any obstacles. Translated with DeepL.com (free version)